Sūrah Al-Fātiḥah as an Antidote: Qur’an and Hadith Reception in Malay Communities of Pontianak and Singkawang - Syamsul Kurniawan; Ihsan Nurmansyah; Azid , Muhammad Adam Abd.; Suratman, Bayu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Initially, Sūrah Al-Fātiḥah was predominantly received by scholars with a focus on textual analysis.However, its reception has expanded, incorporating various practices within communities, including its useas a remedy believed to cure ailments. This study aims to examine the belief in the efficacy of Sūrah AlFātiḥah as a healing remedy among the Malay communities of Pontianak and Singkawang. A qualitativeresearch methodology was employed, analyzed through Ahmad Rafiq’s theory of functional reception. Datawere gathered through observations, interviews, and related literature. The findings reveal that the Malaycommunities of Pontianak and Singkawang believe in Sūrah Al-Fātiḥah’s healing properties based on aHadith stating: “The Opening of the Book serves as a remedy for various ailments.” Performatively, inPontianak, Sūrah Al-Fātiḥah is recited in one breath over a glass of water, which is then consumed by theill. In Singkawang, there are two ways: first, reciting Sūrah Al-Fātiḥah while directing the thumb to theroof of the mouth and applying it to the affected area; second, reciting the surah over water, which is thenconsumed and applied to the afflicted area. The transmission of this knowledge in Pontianak is linked toKitab Mujarabat (literally: Book of Remedies) by Daeng Matse, while in Singkawang, it derives fromKitab Harian (literally: Book of Daily Guidance) by Datok Ngah Dolah. This study contributes to theunderstanding of Living Qur’an and Hadith, revealing a model of acculturative religious education. Thetheoretical, practical, and methodological contributions of this research offer recommendations for futurestudies, such as developing new methods or expanding research datasets